PROBLEMATIKA BENTUK AMAR DAN PENGARUHNYA TERHADAP ISTIMBAT FIQH - Syaikhul Hakim (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
Kalam al-amr (command word) is a form of word that is widely used in the Islamic law (shari'ah) either in the Qur'an and hadith. The word could raise multiple interpretations. The interpretation of kalam al-amr aims to know the meaning of a text to understand the laws contained therein. Basically, differences in interpreting the meaning of Kalam al-amr among Muslim scholars can be concluded that the Kalam al-amr generally indicates the meaning of obligatory, but it can be changed if it indicates other meanings, as well Kalam al-amr can show the meaning of ikrar or vice versa when any evidence that shows the meaning. Differences in interpreting the meaning of Kalam al-amr have implications on how to understand a proposition that ultimately leads to the different conclusions.